2016 IEEE 17th International Symposium on a World of Wireless, Mobile and Multimedia Networks (WoWMoM) 2016
DOI: 10.1109/wowmom.2016.7523554
|View full text |Cite
|
Sign up to set email alerts
|

Population estimation from mobile network traffic metadata

Abstract: Smartphones and other mobile devices are today pervasive across the globe. As an interesting side effect of the surge in mobile communications, mobile network operators can now easily collect a wealth of high-resolution data on the habits of large user populations. The information extracted from mobile network traffic data is very relevant in the context of population mapping: it provides a tool for the automatic and live estimation of population densities, overcoming the limitations of traditional data source… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
(40 reference statements)
0
26
0
Order By: Relevance
“…The approach in [15] mimics several of our solutions, as originally presented in [24]. It leverages regressions on the power-law model of population density in (2), where it uses the number of subscribers at 7 am as the σ i variable: this is semantically similar, but not identical, to the subscriber presence we employ as σ i .…”
Section: Dynamic Populationmentioning
confidence: 99%
“…The approach in [15] mimics several of our solutions, as originally presented in [24]. It leverages regressions on the power-law model of population density in (2), where it uses the number of subscribers at 7 am as the σ i variable: this is semantically similar, but not identical, to the subscriber presence we employ as σ i .…”
Section: Dynamic Populationmentioning
confidence: 99%
“…Researchers have established connections between the underlying population distribution obtained from census estimates with telecommunications data [19]. A recent study demonstrated that "presence" information (i.e., an estimate of the number of users in a certain space based on their last interaction with the mobile network) can provide better correlation with census data [7]. The same study also proposed a method to evaluate real-time population distribution and showed reasonable results, although ground truth was not available.…”
Section: B Mobile Phone Databases For Population Estimationmentioning
confidence: 99%
“…Khodabandelou et al [7] proposed the use of mobile activity and census data to provide a real-time population estimate. A model was established using overnight values and census data.…”
Section: B Mobile Phone Activity Data Analysismentioning
confidence: 99%
See 2 more Smart Citations